ANALISIS PENGENDALIAN MUTU TIKAR LAMPIT ROTAN (RATTAN CARPET) MENGGUNAKAN SNI 12-0677-2002 DI PT SARIKAYA SEGA UTAMA BANJARBARU KALIMANTAN SELATAN - Adri Haufifatih; Zainal Abidin; Siti Hamidah (Universitas Lambung Mangkurat, 2023)
Rattan carpet produced by PT Sarikaya Sega Utama have not yet used the SNI 12-0677-2002 standard.This study aims to analyze the quality of rattan carpet using general and special parameter requirements that have been regulated in SNI 12-0677-2002 and the results of these tests are analyze for product quality control using a cause and effect diagram/fishbone diagram. The test result for 11 parameters of general requirements measured using a tool obtain 54% fulfilled according to SNI with details of 6 of 11 parameters fulfilled, namely thickness, width and distance of hijiran holes, witdh of tulang walut, thickness of watun and water content. The results of testing the parameters of general requirements observed visually obtained 50% fulfilled according to SNI with details 2 of 4 parameters fulfilled, namely eveness and type of yarn. The results of testing the special requirements measured using tools and observed visually obtained 33,3% fulfilled according to SNI with details 1 of 3 parameters being met, namely the natural color of the upper surface of the lampit. Based on SNI 12-0677-2002 the production of rattan carpet at PT Sarikaya Sega Utama is not yet in a controlled state because all the reference parameters that have been regulated in SNI 12-0677-2002 have not been fulfilled. The cause of the failure is caused by human error, machine (equipment) and material (raw materials).Tikar lampit rotan yang di produksi oleh PT Sarikaya Sega Utama sampai saat ini belum menggunakan standar SNI 12-0677-2022. Penelitian ini bertujuan untuk menganalisis kualitas tikar lampit menggunakan parameter persyaratan umum dan khusus yang telah diatur di dalam SNI 12-0677-2002 dan hasil pengujian tersebut di analisis pengendalian mutu produk menggunakan diagram sebab akibat/tulang ikan. Hasil pengujian 11 parameter persyaratan umum yang diukur menggunakan alat didapatkan hasil 54% sesuai SNI dengan rincisan 6 dari 11 parameter terpenuhi yaitu tebal, lebar dan jarak lubang hijiran, lebar tulang walut, tebal watun serta kadar air. Hasil pengujian parameter persyaratan umum yang diamati secara visual didapatkan hasil 50% sesuai SNI dengan rincisan 2 dari 4 parameter terpenuhi yaitu kerataan dan jenis benang. Hasil pengujian persyaratan khusus yang diukur menggunakan alat dan diamati secara visual didapatkan hasil 33,3% sesuai SNI dengan rincisan 1 dari 3 parameter terpenuhi yaitu warna alami permukaan atas lampit. Berdasarkan SNI 12-0677-2002 produksi tikar lampit rotan di PT Sarikaya Sega Utama belum di dalam keadaan terkendali sebab belum terpenuhinya ke seluruh parameter acuan yang telah diatur di dalam SNI 12-0677-2002. Penyebab dari kegagalan tersebut disebabkan oleh faktor kesalahan manusia (human error), mesin (alat) dan material (bahan baku).